ARTHROSCOPIC TREATMENT OF POSTERIOR ANKLE IMPINGEMENT IN PEDIATRIC ATHLETES AND ITS OUTCOMES - A PROSPECTIVE STUDY. Issue 7 (30th July 2021) - Kushare, Indranil; Ghanta, Ramesh; Allahabadi, Sachin; Kastan, Kristen; Stone, Tracie; Gomez, Jorge; McKay, Scott
Background: Posterior ankle impingement (PAI) is a known cause of posterior ankle pain in athletes performing repetitive plantarflexion motions, such as in soccer. Even though it is well-described in adults, literature on PAI in pediatric patients is scarce. Purpose: The purpose was to describe prospective outcomes after arthroscopic management of posterior ankle impingement in pediatric and adolescent patients. Methods: An IRB-approved prospective study was performed at a tertiary children's hospital from 2016-2020. Patients <18 years of age who were diagnosed with posterior ankle impingement and underwent posterior ankle arthroscopy with minimum 3-month post-operative follow-up were included. Data collected included pre-operative demographics and sporting activities, clinical and radiologic findings. Visual Analogue Scale (VAS) scores, and American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot scores were collected at the initial and follow-up visits. Results: A total of 50 patients (65 ankles; 28 females), were included with mean age 13.3 years. Football and soccer were the most commonly implicated sports. All patients underwent initial conservative management including relative rest, immobilization and/or physical therapy for an average period of 44 weeks. The indication for surgery was failure of conservative management to improve symptoms. All patients underwent posterior ankle arthroscopy with arthroscopic confirmation of impingement pathology followed by debridement. The pathology was predominantly bony (Os trigonum, Stieda process) in 54%, and predominantly soft tissue (low flexor hallucis longus belly, ganglion cyst in the ankle, hypertrophied posterior ankle ligaments) in 46%. All 50 patients (100%) returned to sports at an average 8.5 ± 4.1 weeks. 51 ankles had radiographs done at 1 years post-operatively which did not show recurrence or any new osseous abnormalities. At mean follow up of 26 months, there was a statistically significant improvement in VAS scores (7.0 to 0.53, p<0.05) and AOFAS scores (63.9 to 95.6, p<0.05) from pre- to post-operative final follow-up. Complications included numbness over lateral part of the heel (sural nerve distribution) in 1 patient. Conclusion: The first prospective study on pediatric PAI demonstrates that arthroscopic treatment, after failed conservative management, allowed patients to return to prior level of activity and sports, and resulted in improved pain relief and higher functional parameters. Complications associated with this procedure were minimal.